Strategic Analysis of Export Activities of Enterprises to Ensure Sustainable Development - Pakhucha, Elina; Babko, Natalia; Bilousko, Tamila; Bilousko, Roman; Vynohradenko, Serhiy; Azizov, Otabeg (European Journal of Sustainable Development, 2021)
In the article necessity and significance to study of financial risks, which are a constant factor in the activity of any enterprise, are substantiated. It is established that for a broader understanding of the essence of financial risk it is necessary to consider it as a cumulative risk of the enterprise. The growing impact of financial risks on the results of financial and economic activities is associated with the uncertain economic situation, the instability of financial market conditions, the rapid introduction of new financial technologies and financial instruments, expanding the scope of financial relations of the enterprise. Methods of financial risk assessment are investigated, which involve the identification of risks, determining the causes of their occurrence and potential risk areas, as well as the negative consequences of making a risky decision or possible benefits. Comparing the methods of quantitative assessment of financial risk, it was found that the level of risk may vary depending on the chosen method of assessment. A system of financial ratios has been formed to quantify the risk of enterprises of different sizes, namely for large, medium and small enterprises, which most accurately reflect the current financial situation. An assessment of the financial results of enterprises operating in the field of wholesale trade. The financial results before the taxation of activity as an indicator that characterizes the potential for profit generation of wholesale trade enterprises by size distribution are studied. The value of financial results (balance) before taxation of wholesale trade enterprises is forecasted. It is established that the growing pressure of the crisis and insecurity on the part of the state will lead to the transition from the crisis in which enterprises are today, to a state of economic bankruptcy. This situation requires the formation and use of financial resources of enterprises, based on the system and complexity of making and implementing management decisions. Quantitative and qualitative assessment of financial risks of wholesale trade enterprises belonging to groups of large, medium and small enterprises was carried out. Based on these calculations, the ranking of priorities in the management of financial stability. It is established that the first place among the blocks of financial coefficients of risk assessment of enterprises is occupied by the block of business activity, then the block of profitability indicators, the block of liquidity indicators, the final block of capital structure. For each of the defined blocks the directions of increase, or optimization that will provide financial stability of the enterprise are presented.